Simple mathematical approach to solar cell/panel behavior based on datasheet information. (April 2017) - Pindado, Santiago; Cubas, Javier
Abstract: A new explicit mathematical expression is used to describe the behavior of a photovoltaic device (solar cell/panel), that is, its I - V curve, based on the characteristic points normally included in the manufacturers' datasheets. This expression consists of two simple equations, one for voltage levels lower than the voltage at the maximum power point, V < V mp, and the other one for voltage levels above this point, V > V mp . The first equation is defined with two of the three characteristic points (short circuit and maximum power points), whereas the second one is defined with the current and voltage levels at maximum power point, the open circuit voltage, and a constant that can be adjusted based on: 1) the best fitting to the data within the bracket [ V mp, V oc ], or 2) one point within this bracket, or 3) the slope of the I - V curve at the open circuit point, or 4) an estimation of that slope. Results of the solar cell/panel behavior analysis obtained with the proposed methodology, are similar to the ones obtained with the well-known 1-diode/2-resistor equivalent circuit model, in terms of accuracy. Highlights: A 2-equations method to estimate photovoltaic solar cell/panel is developed. This method is quick, accurate and reliable. It is based only on the information from manufacturer's datasheet.